Understanding Inclusion. (2nd February 2022) - Brix, Kaja A; Lee, Olivia A; Stalla, Sorina G
Abstract: The understanding and practice of inclusion are critical to realizing the full benefits of diverse representation. Little research on inclusion within diversity contexts exists. We examined the meaning of inclusion through crowdsourcing and a grounded theory methodology of data analysis and theory development. We collected responses to the question "What does inclusion mean to you?" The data revealed concepts of empathy, warmth, support, love, acceptance and curiosity; diverse perspectives; and participation. Our theoretical model suggests a dynamic process of inclusion operating from principal structural elements: a foundation that involves place, access and participation, and space; reciprocal engagement as an engine for inclusion; and expression of inclusion as culture. This understanding provides a structured means by which inclusion can be practiced.